Patients and performative identities at the intersection of the Mesopotamian technical disciplines and their clients - Johnson, Justin Cale, 1971- (Rencontre assyriologique internationale, 2020)
"A collection of essays investigating how Mesopotamian technical specialists interacted with their clients and in doing so forged their social and professional identities"--